Living donor liver transplantation for combined hepatocellular-cholangiocarcinoma: A case series of four patients. (2020) - Ito, Takashi; Ishii, Takamichi; Sumiyoshi, Shinji; Ogiso, Satoshi; Fukumitsu, Ken; Ito, Takashi; Yagi, Shintaro; Seo, Satoru; Hata, Koichiro; Taura, Kojiro; Uemoto, Shinji
Highlights: Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a rare primary liver carcinoma. The indications for live transplantation for cHCC-CCA remain controversial. In this case series, patients who met the Milan criteria on the pathological examination had good prognosis. By itself, cHCC-CCA was not a contraindication for liver transplantation. Abstract: Introduction: Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a rare primary liver carcinoma whose components include both hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA). Indications for liver transplantation for cHCC-CCA remain controversial. Case presentations: Four patients underwent living donor liver transplantation (LDLT) for cHCC-CCA. All patients had multiple tumor nodules preoperatively diagnosed as HCC. Postoperative pathological examinations revealed that one of the tumors was cHCC-CCA. Cases 1 and 2 underwent LDLT for cirrhosis with HCC tumors that met Milan criteria. Case 3 underwent LDLT for recurrent HCC tumors with nonalcoholic steatohepatitis. Although the preoperative examinations showed that the patient met the Kyoto, but not Milan criteria, postoperative pathological examinations revealed that the patient did meet Milan criteria. The three patients who met Milan criteria on postoperative pathological examination had no recurrences after LDLT. Case 4 had multiple tumors with alcoholic liver cirrhosis. Although the preoperative examinations showed that the patient did not meet Milan criteria—but did meet Kyoto criteria—, on postoperative pathological examinations, the patient met neither Millan nor Kyoto criteria. He died of tumor recurrence 15 months after LDLT. Discussion and conclusions: Our experiences suggested that patients who meet Millan or Kyoto criteria experienced acceptable outcomes of LDLT for cHCC-CCA. By itself, cHCC-CCA is not contraindication for liver transplantation.